Pengaruh Volume Penyiraman Air Dan Kompos Kulit Buah Kakao Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) Pada Medium PMK Di Pembibitan Utama - Dedi Setiawan Marpaung; Ardian Ardian; Erlida Ariani Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of the watering volume and cocoa pod husks compost in the RYP medium as well as to get the best treatment combination on the growth of oil palm (Elaeis guineensis Jacq.) seedlings in the main nursery. This research was conducted in the greenhouse of Faculty of Agriculture, University of Riau, Pekanbaru, from December 2015 to March 2016. This research conducted as an experiment using a completely randomized design (CRD) and 3 replications. Each experimental unit had 2 seedlings. Parameters those measured were seedling height, leaves number, trunk diameter growth, roots to shoot ratio, and dry weight. Data were analyzed statistically using ANOVA and Duncan's Multiple Range's at the tier of 5%. The results suggest that the interaction of watering volume and cocoa pod husks compost had no significant effect on all parameters, but watering volume significantly affected dry weight. While cocoa pod husks compost significant effect on seedling height and seedling dry weight. In implementation of 2.5 l / polybag watering volume and 200g / polybag cocoa pod husks compost provide the best treatment to all parameters. Keywords: oil palm, water volume watering, cocoa pod husks compost